Rhinovirus-induced airway disease : A model to understand the antiviral and Th2 epithelial immune dysregulation in childhood asthma (2015)
Rhinovirus (RV) infections account for most asthma exacerbations among children and adults, yet the fundamental mechanism responsible for why asthmatics are more susceptible to RV than otherwise healthy individuals remains largely unknown. Nonetheless, the use of models to understand the mechanisms of RV-induced airway disease in asthma has dramatically expanded our knowledge about the cellular and molecular pathogenesis of the disease. For instance, ground-breaking studies have recently established that the susceptibility to RV in asthmatic subjects is associated with a dysfunctional airway epithelial inflammatory response generated after innate recognition of viral-related molecules, such as double-stranded RNA. This review summarizes the novel cardinal features of the asthmatic condition identified in the past few years through translational and experimental RV-based approaches. Specifically, we discuss the evidence demonstrating the presence of an abnormal innate antiviral immunity (airway epithelial secretion of types I and III interferons), exaggerated production of the master Th2 molecule thymic stromal lymphopoietin, and altered antimicrobial host defense in the airways of asthmatic individuals with acute RV infection.